2022
DOI: 10.1039/d1tc05453h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous microwave-assisted reduction and B/N co-doping of graphene oxide for selective recognition of VOCs

Abstract: Herein, the influence of heteroatom domains on the volatile organic compounds (VOCs) detection properties of B/N co-doped graphene oxide nanostructures was investigated by using different boron (B) and nitrogen (N)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…These values of the sensitivity and LoD are good and even better than some 2D materials operating at room temperature reported in the literature. 36 The stability is also an important sensing parameter for practical application of a sensor device. The stability of 2D titanium carbo-oxide material was thus investigated by measuring the response towards methanol using our device that has been stored at room temperature.…”
Section: Gas-sensor Applicationsmentioning
confidence: 99%
“…These values of the sensitivity and LoD are good and even better than some 2D materials operating at room temperature reported in the literature. 36 The stability is also an important sensing parameter for practical application of a sensor device. The stability of 2D titanium carbo-oxide material was thus investigated by measuring the response towards methanol using our device that has been stored at room temperature.…”
Section: Gas-sensor Applicationsmentioning
confidence: 99%
“…2.69 (N), 1.41 (B) Reduced graphene oxide nanosheets [41] [d] NaBPh 4 + ACN 12.4 (N), 6.9 (B) [42] rGO + [e] H 3 N-BH 3 2.6 (N), 7.3 (B) [43] Solvothermolysis and Thermal annealing…”
Section: Chemical Vapour Deposition (Cvd)mentioning
confidence: 99%
“…For instance, metal oxides doped with Sc [28] and Ag [29] atoms exhibited enhanced sensor performance toward VOCs in contrast with their pure phase. Additionally, it has been reported that B [30], N [31], and Li [32] atoms doping could effectively enhance the selective recognition of carbon-based materials toward VOCs and ammonia. In addition, previous theoretical studies have reported that metal (e.g., Al and Ti)-doped C 2 N were potential sensing materials for certain VOCs [27,33].…”
Section: Introductionmentioning
confidence: 99%